Peripheral myelin protein-22 (PMP22) modulates alpha 6 integrin expression in the human endometrium - Braun Jonathan; Gordon Lynn K; Amici Stephanie; Hogue Claire P; Sudhakar Deepthi; Rao Rajiv G; Notterpek Lucia; Goodglick Lee; Wadehra Madhuri (BMC, 2011)
Abstract Background PMP22, a member of the GAS3 family of tetraspan proteins, is associated with a variety of neurological diseases. Previous studies have shown that PMP22 is expressed in proliferative endometrium, but its function within this tissue is poorly understood. In this study, we first characterized the expression of PMP22 in the human menstrual cycle and began to characterize its function in the endometrium. Methods Using a combination of immunohistochemistry and quantitative PCR, we characterized the expression of PMP22 in both proliferative and secretory endometrium. Differences in PMP22 expression between proliferative and secretory endometrium were determined using a Mann-Whitney U test. In order to investigate the influence of PMP22 on α6 integrin expression, cells were created that ectopically overexpressed PMP22 or expressed a siRNA to inhibit its expression. These cells were analyzed for changes in integrins and binding to extracellular matrices. Results In this study, we show that PMP22 expression is higher in proliferative phase than secretory phase. Functionally, we have begun to characterize the functional significance of this expression. Previous studies have suggested a link between PMP22 and α6 integrin, and therefore we asked whether PMP22 could associate or potentially modulate the expression of α6 integrin. Expression of both PMP22 and α6 integrin were detectable in endometrial epithelial and stromal cells, and we show that both proteins can associate and colocalize with each other. To understand if PMP22 directly altered the expression of a6 integrin, we examined cell lines with modulated levels of the protein. Overexpression of PMP22 was sufficient to increase α6 integrin surface expression with a concominant increase in binding to the extracellular matrix laminin, while a reduction in PMP22 suppressed α6 integrin surface expression. Conclusion These findings suggest a physiologic role for PMP22 on the expression of α6 integrin. We predict that this may be important for the maintainence of endometrial integrity and to the disease biology associated with altered levels of α6 integrin expression in the endometrium.